2021
DOI: 10.1039/d1ma00659b
|View full text |Cite
|
Sign up to set email alerts
|

First demonstration of the use of open-shell derivatives as organic luminophores for transparent luminescent solar concentrators

Abstract: Luminescent Solar Concentrators (LSCs) are rapidly emerging as key enabling technology towards the realization of zero energy buildings. The development of new efficient and sustainable luminophores is crucial for further...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…In general, it has been reported that the addition of a donor on a radical improved the photostability of the radicals. 2 e,f ,3 b ,10,11,13 d ,15 Considering that the photostability of PyBTM was 71 times that of TTM in dichloromethane and 45 times that of TTM in cyclohexane, and that it was even comparable to closed-shell molecules with a long π-system such as TIPS pentacene, 7 a the improved photostability of 1 , 2 , and 3 showed excellent values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it has been reported that the addition of a donor on a radical improved the photostability of the radicals. 2 e,f ,3 b ,10,11,13 d ,15 Considering that the photostability of PyBTM was 71 times that of TTM in dichloromethane and 45 times that of TTM in cyclohexane, and that it was even comparable to closed-shell molecules with a long π-system such as TIPS pentacene, 7 a the improved photostability of 1 , 2 , and 3 showed excellent values.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we made the first report on the use of a radical as an organic luminophore for a transparent luminescent solar concentrator (LSC). 11 A PyBTM derivative having phenyl groups para to the a-carbon: (3,5-dichloro-4-pyridyl)bis (2,6-dichloro-4-phenylphenyl)methyl radical (PyPBTM) provided a particularly suitable combination of emission efficiency and separation between absorption and emission spectra. The selective substitution of the 4-chloro group of aH-PyBTM (precursor of PyBTM) was achieved with the development of the Suzuki-Miyaura coupling reaction with micellar catalysis (Micellar Suzuki-Miyaura MSM).…”
Section: Introductionmentioning
confidence: 99%
“…Beverina et al 98 reported the first demonstration of PyBTM-based D–A structures for use as luminophores in luminescent solar concentrators (LSCs), where by default the radicals must be thermally and photochemically stable (Fig. 7).…”
Section: Carbon-centred π-Radicals Their Properties and Applicationsmentioning
confidence: 99%
“…8 The practical demonstration of radical-based OLEDs with doublet emission paved the way for the development of novel luminescent neutral radicals and OLED device architecture optimization. [9][10][11] So far, the chemical space has been principally limited to the TTM, 12 perchlorotriphenylmethyl (PTM) 13 and bis(2,4,6-trichlorophenyl)methyl (BTM) [14][15][16] radical families. Recently, Li and co-workers reported what is to date the most efficient radical-based OLED (TTM-3NCz), reaching an impressive external quantum efficiency (EQE) of 27%.…”
Section: Introductionmentioning
confidence: 99%